Effective Commands to Overcome Students with Disruptive Behavior in the Classroom - Kusumadewi, Luh Kade Diana; Adnyani, Luh Diah Surya; Pratiwi, Ni Putu Astiti (ENGLISH FRANCA : Academic Journal of English Language and Education, 2020)
This study was conducted which aimed at investigating effective commands used by teachers in TK Aura Sukma Insani to overcome disruptive behaviors by identifying: 1) the types of disruptive behavior done by students, 2) the types of command used by the teachers, and 3) the commands which are effective based on students’ responses. Teachers and students from A2, A1, and toddler class were the subject of the study while disruptive behaviors done by the students and commands used by the teacher were the object of the study. All the data were gathered through observation, questionnaire, and interview. The result revealed that there were 145 disruptive behaviors found and seven type of commands used by the teachers including question command, regular command, indirect command, don’t command, stop command, negative command and other command. Moreover, most of the commands given were effective based on the effects on students’ behavior. From the result, it could be concluded that regular command and other command were the most effective types of command used by teachers to overcome disruptive behaviors because the commands related were clear, understandable, and simple. Therefore, the student were easy to understand what the teachers intended.